Alkaline Stability Evaluation of Polymerizable Hexyl‐Tethered Ammonium Cations. Issue 12 (5th December 2021) - Ertem, S. Piril; Coughlin, E. Bryan
Abstract: One of the important challenges in designing robust alkaline anion exchange membranes is the difficulty associated with the chemical stability of covalently bound cationic units. Here, a systematic study exploring alkaline stabilities of polymerizable hexyltrimethylammonium cations is presented, where the hexyl chain is linked to a phenyl ring through a direct carbon‐carbon, phenyl ether, or benzyl ether functionality. For this work, small molecule model compounds, styrenic monomer analogs, and their homopolymers are synthesized. Alkaline stabilities of the small molecule cations and their homopolymers are compared to alkaline stability of benzyltrimethylammonium (BTMA) cation and its homopolymer poly(BTMA), respectively. All the hexyl‐tethered cations and their homopolymers are significantly more stable under strongly alkaline conditions (2 m KOD at 80 °C). Moreover, ether‐linked cations show comparable stability to the direct carbon‐carbon linked cation. Via 1 H NMR analyses, possible degradation mechanisms are investigated for each small molecule cation. Findings of this study strongly suggest that the alkaline stability is dictated by the steric hindrance around the β ‐hydrogen. This study expands beyond the limits of general knowledge on alkaline stability of alkyl‐tethered ammonium cations via the Hofmann elimination route, highlights important design parameters for stable ammonium cations, and demonstrates accessible directly polymerizable alkaline stable ammonium cations. Abstract : Alkaline stabilities of trimethylammonium cations with a hexyl‐tether are studied via 1 H NMR under strongly alkaline conditions (2 m KOD at 80 °C). All cations and their homopolymers show significantly improved alkaline stability compared to the benchmark benzyltrimethylammonium cation and its homopolymer, independent of the linker chemistry utilized to attach the hexyl chain to the phenyl head.